SK2 channels are required for function and long-term survival of efferent synapses on mammalian outer hair cells - Murthy, Vidya (2009)
Cochlear hair cells use SK2 currents to shape responses to cholinergic efferent feedback from the brain. Using SK2-/- mice, we demonstrate that, in addition to their previously defined role in modulating hair cell membrane potentials, SK2 channels are necessary for long-term survival of olivocochlear fibers and synapses. Loss of the SK2 gene also results in loss of electrically driven olivocochlear effects in vivo, and down regulation of ryanodine receptors involved in calcium-induced calcium release, the main inducer of nAChR evoked SK2 activity. Generation of double-null mice lacking both the α10 nAChR gene, loss of which results in hypertrophied olivocochlear terminals, and the SK2 gene, recapitulates the SK2-/- synaptic phenotype and gene expression, and also leads to down regulation of α9 nAChR gene expression. The data suggest a hierarchy of activity necessary to maintain early olivocochlear synapses at their targets, with SK2 serving an epistatic, upstream, role to the nAChRs.